Quantum-Inspired Uncertainty Quantification - Wirsching, Günther (Frontiers in Computer Science, 2022)
Reasonable quantification of uncertainty is a major issue of cognitive infocommunication, and logic is a backbone for successful communication. Here an axiomatic approach to quantum logic, which highlights similarity to and differences to classical logic, is presented. The axiomatic method ensures that applications are not restricted to quantum physics. Based on this, algorithms are developed which asign to an incoming signal a similarity measure to a pattern generated by a set of training signals.